UPAYA KETUA YAYASAN DALAM MENINGKATKAN KINERJA PENGELOLA PENDIDIKAN DI SMK PANTI PAMARDI SIWI (PPS) 2 NGRAMBE - Luluk Muashomah (Institut Agama Islam Ngawi, 2022)
Abstract: The position of the chairman of the foundation as the organizer of an educational institution requires the professionalism of the profession. This requires a new mechanism such as special education to become school principals. Therefore, the appointment of school principals, who have been based on long experience as teachers, should be equipped with special education for school principals. Panti Pamardi Siwi Ngrambe Vocational School is a top-level public education institution that plays a role in guiding the younger generation, especially to become servants who are able to carry out life's tasks in the world. the head of the foundation and the manager of general education, especially in these educational institutions, are responsible for the trust of parents to continue their unfinished education. This study shows how the performance of the chairman of the Panti Pamardi Siwi Ngrambe Vocational School foundation has an effect on improving the performance of managers. The performance can be in the form of academic performance or non-academic performance. Academic performance is a performance related to the results of the evaluation of the principal, including the manager. Meanwhile, non-academic performance can be in the form of non-academic activities that are attended by the manager of Panti Pamardi Siwi Ngrambe Vocational School such as comparative studies, workshops and the like. Based on these efforts, the role of the foundation on the performance of the management of SMK Panti Pamardi Siwi 2 Ngrambe is currently quite satisfactory, both academic and non-academic. Keywords: Panti Pamardi Siwi Vocational School 2 Ngrambe, Chair of the Foundation, and Education Manager.